Emergent literacy beliefs in preschool and kindergarten contexts - Lopes, João A. (2009)
This study aims to understand how a group of preschool/kindergarten teachers (N = 340) perceives and accomplishes linguistic and literacy oriented practices. Results show that, in a set of literacy and language tasks, teachers tend to value oral driven tasks and seldom engage in activities that relate to teaching the written language. This profile of educators is a reflection of prevalent views in pre-service teacher education and of some of the most common practices in Portuguese preschool and kindergarten classes (ages 3-6) and suggests that teachers have limited scientific knowledge of emergent literacy concepts. It seems that, despite being promoted to university training in the last 20 years, pre-service education does not yet reflect the state of the art in early childhood education. In a set of in-depth interviews (N = 8) we found a close association between the absence of literacy practices and the absence of pre-service specific knowledge about this subject. Participants that report consistent and regular linguistic and literacy oriented practices seem to perceive pre-service education as critical for their commitment to those practices. On the other hand, older teachers and teachers with lower training levels seem to undervalue specific literacy oriented tasks. The opposite seems to happen with younger and more educated teachers. Overall, our study suggests that the contents of pre-service and in-service education induce specific practices in preschool/kindergarten contexts, but it also suggests that this impact may be limited by socialization effects of dominant professional practices.